Usage of Rice Husk for the Production of Low-Temperature Cement: Physico-Chemical and Technological Aspects - Dorohan, Nataliia; Chernyak, Lev; Sviderskyy, Valentin; Pakhomova, Victoria; Shnyruk, Oleg (Київський національний університет імені Тараса Шевченка, 2025)
The aim of the work was to deepen scientific understanding of the physicochemical aspects of phase formation of silicate systems of the CaO-SiO2-Al2O3 type when using rice husk as a silica-containing component of technogenic origin. The research methods included a complex of chemical, X-ray phase analyses, computer calculations and technological testing of materials. Based on the analysis of the results of calculations regarding compliance with the required values of the cement modulus characteristics, possible quantitative ratios of the carbonate component and rice husk were determined. As a result of technological testing, the compositions of the initial binary mixture based on marl with a content of up to 28 wt. % rice husk were determined, which ensures the production of a mineral binder - an analogue of Roman cement with an increase in strength indicators by 1.5 times. According to the data of X-ray phase analysis, the peculiarities of physicochemical transformations during the firing of the compositions were established, which are associated with the increased reactivity of amorphous rice husk silica to phase formation with a change in the quantitative ratio of crystalline phases of calcium silicates, the development of C2AS and A3S2 phases distributed in the glass phase. A conclusion was made about the possibility and feasibility of using rice husk to produce cement fired by low temperature for a comprehensive solution to the issues of chemical technology and resource saving.
Keywords: binder; raw material; composition; phase formation; properties